Laboratory Verification of a BRCA1 and BRCA2 Massively Parallel Sequencing Assay from Wet Bench to Bioinformatics for Germline DNA Analysis - Poon, Kok-Siong; Chiu, Lily; Tan, Karen Mei-Ling (Global Medical Genetics, 2021)
Introduction A robust genetic test for BRCA1 and BRCA2 genes is necessary for the diagnosis, prognosis, and treatment of patients with hereditary breast and ovarian cancer. We evaluated a commercial amplicon-based massively parallel sequencing (MPS) assay, BRCA MASTR Plus on the MiSeq platform, for germline BRCA genetic testing.Methods This study was performed on 31 DNA from cell lines and proficiency testing samples to establish the accuracy of the assay. A reference cell line DNA, NA12878 was used to determine the reproducibility of the assay. Discordant MPS result was resolved orthogonally by the current gold-standard Sanger sequencing method.Results The analytical accuracy, sensitivity, and specificity for variant detection were 93.55, 92.86, and 100.00%, respectively. Both sequencing depth and variant allele frequencies were highly reproducible by comparing the NA12878 DNA tested in three separate runs. The single discordant result, later confirmed by Sanger sequencing was due to the inability of the MASTR Reporter software to identify a 40-bp deletion in BRCA1.Conclusion The BRCA MASTR Plus assay on the MiSeq platform is accurate and reproducible for germline BRCA genetic testing, making it suitable for use in a clinical diagnostic laboratory. However, Sanger sequencing may still serve as a confirmatory method to improve diagnostic capability of the MPS assay.
Keywords: BRCA1; BRCA2; massively parallel sequencing; NGS; Multiplicom